Akuntabilitas Dan Transparansi Pengelolaan Alokasi Dana Desa Dalam Perspektif Administrasi Hukum Di Desa Matinan Kabupaten Buol - Alhamid Baharuddin (Universitas Muhammadiyah Ponorogo, 2026)
This study examines the management of Village Fund Allocation (ADD) in Matinan Village, Gadung District, Buol Regency, by examining the accountability and transparency aspects from an administrative law perspective. This study uses an empirical legal method with a socio-legal approach. Data were obtained through interviews, observation, and documentation, then analyzed qualitatively by assessing the conformity of ADD management practices with the principles of legality, AUPB, good governance principles, and village financial management regulations. The results indicate that accountability in ADD management has been implemented through recording, reporting, and accountability. However, its implementation has not been optimal due to obstacles in the use of village financial applications, late reporting, and low public understanding of the report content. Transparency has also been implemented through village deliberations, direct communication, and the provision of financial documents. However, information has not been distributed evenly, community participation is still low, and access to village financial documents is not fully clear. Thus, ADD management in Matinan Village has fulfilled some administrative obligations, but does not fully reflect the principles of administrative law substantively.